2020
DOI: 10.3390/ani10040556
|View full text |Cite
|
Sign up to set email alerts
|

The First Application of Nanoelectrochemotherapy in Feline Oral Malignant Melanoma Treatment—Case Study

Abstract: Background: The aim of this study was to present the first domestic animal trial of nanosecond electroporation with chemotherapy and CO2 laser surgery. Methods: sixteen-year-old domestic cat with diagnosed melanoma on oral cavity was the case used in the study. Firstly, CO2 laser surgery was used for the removal of most of tumor mass. Then nanoelectrochemotherapy with bleomycin was applied including appropriate margin of healthy tissue. A 15 ± 4 kV/cm × 15 ns pulsing protocol was employed with a total of 800 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…15 , 16 Additionally, with nanosecond pulses, the possibility of thermal damage to the tissue is minimized 5 , 6 due to low energy being transferred to the treated area and electrochemical reactions are reduced. 8 ECT with nanosecond pulses has shown promising results 8 , 17 , 18 , 19 , but the underlying mechanisms of the observed decrease in cell survival and tumor regression remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 , 16 Additionally, with nanosecond pulses, the possibility of thermal damage to the tissue is minimized 5 , 6 due to low energy being transferred to the treated area and electrochemical reactions are reduced. 8 ECT with nanosecond pulses has shown promising results 8 , 17 , 18 , 19 , but the underlying mechanisms of the observed decrease in cell survival and tumor regression remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nanosecond pulses have been explored in ECT and calcium electroporation and have shown promising results -either tumor regression in vivo or a decrease in cell survival in vitro. 8,[17][18][19][20][21] We have previously reported that nanosecond pulses of an appropriately chosen amplitude in combination with cisplatin decreased cell survival in in vitro assays to the same extent as standard 8 × 100 μs pulses. 8 The aim of our present work was to investigate the underlying mechanisms of ECT with nanosecond pulses and cisplatin in vitro on Chinese hamster ovary CHO and mouse skin melanoma B16F1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another case study outlined the use of nano-ECT as an adjunct after the CO 2 laser surgical removal of the bulk of an oral melanoma in a cat. 19 Nano-ECT is a form of ECT that delivers a pulsed electric field with a duration of nanoseconds rather than microseconds, 20 as is more commonly used, and which was utilised in this case. In that case report the patient was treated with nanosecond pulses and bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation is still a developing technique and finds usability mainly for drug or gene delivery or in food technology [ 1 , 2 ]. Nanosecond electric pulsed fields (nsPEFs) are mainly applied in food technology known as bio-based industry [ 3 , 4 ], but researchers still demonstrate numerous nsPEFs’ advantages in anticancer protocols [ 5 , 6 , 7 , 8 ]. The nanosecond range of the electric pulses induces various changes in the exposed cells.…”
Section: Introductionmentioning
confidence: 99%